Gastric cancer: immunohistochemical classification of molecular subtypes and their association with clinicopathological characteristics - Eva-Maria Birkman; Naziha Mansuri; Samu Kurki; Annika Ålgars; Minnamaija Lintunen; Raija Ristamäki; Jari Sundström; Olli Carpén (Springer Berlin Heidelberg, 2022)
Gastric cancer is traditionally divided into intestinal and diffuse histological subtypes, but recent molecular analyses have led to novel classification proposals based on genomic alterations. While the intestinal- and diffuse-type tumours are distinguishable from each other at the molecular level, intestinal-type tumours have more diverse molecular profile. The technology required for comprehensive molecular analysis is expensive and not applicable for routine clinical diagnostics. In this study, we have used immunohistochemistry and in situ hybridisation in molecular classification of gastric adenocarcinomas with an emphasis on the intestinal subtype. A tissue microarray consisting of 244 gastric adenocarcinomas was constructed, and the tumours were divided into four subgroups based on the presence of Epstein-Barr virus, TP53 aberrations and microsatellite instability. The intestinal- and diffuse-type tumours were separately examined. The distribution of EGFR and HER2 gene amplifications was studied in the intestinal-type tumours. Epstein-Barr virus positive intestinal-type tumours were more common in male patients (p = 0.035) and most often found in the gastric corpus (p = 0.011). The majority of the intestinal-type tumours with TP53 aberrations were proximally located (p = 0.010). All tumours with microsatellite instability showed intestinal-type histology (p = 0.017) and were associated with increased overall survival both in the univariate (p = 0.040) and multivariate analysis (p = 0.015). In conclusion, this study shows that gastric adenocarcinomas can be classified into biologically and clinically different subgroups by using a simple method also applicable for clinical diagnostics.